2020
DOI: 10.3390/app10124255
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Analysis of IR Thermography Data for Differentiating Glass Types in Historical Leaded-Glass Windows

Abstract: Infrared thermography is a fast, non-destructive and contactless testing technique which is increasingly used in heritage science. The aim of this study was to assess the ability of infrared thermography, in combination with a data clustering approach, to differentiate between the different types of historical glass that were included in a colorless leaded-glass windows during previous restoration interventions. Inspection of the thermograms and the application of two data mining techniques on the thermal data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Several studies have been conducted to investigate the effects of various experimental parameters on thermal measurement accuracy. The United States Food and Drug Administration 40 quantitatively compared two moderately priced commercial IRTs in various environmental conditions. The study found that the temperature, humidity, and type of data processing methods significantly affected IRT results.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to investigate the effects of various experimental parameters on thermal measurement accuracy. The United States Food and Drug Administration 40 quantitatively compared two moderately priced commercial IRTs in various environmental conditions. The study found that the temperature, humidity, and type of data processing methods significantly affected IRT results.…”
Section: Introductionmentioning
confidence: 99%
“…Further processing of the data, such as application of clustering algorithms, might result in more reliable results, based on the entire time sequence of recorded thermograms. [ 34 ]…”
Section: Resultsmentioning
confidence: 99%
“…The ensuing thermal anomalies were investigated by acquiring a series of thermograms at a frame rate of 10 Hz. [ 34–37 ]…”
Section: Methodsmentioning
confidence: 99%
“…• masonry quality and texture; • connections among structural elements; • structural irregularities or defects; • presence of damages and phenomena of degradation. In this context the use of advanced close-range non-destructive techniques, such as Infrared Thermography (IRT) can already be profitably used for the detection of conservation issues (e.g., open fractures, unstable ledges) that can lead to deterioration phenomena (Hillen 2020, Meola 2016, Enshaeian 2021). These techniques, when combined with traditional methods (e.g.…”
mentioning
confidence: 99%